PENYULUHAN KESEHATAN DENGAN METODE BRAINSTORMING DAN SIMULATION GAME TERHADAP PENGETAHUAN REMAJA PEREMPUAN TENTANG MENSTRUASI - Novita Br Ginting Munthe; Iskandar Markus Sembiring; Sri Wulan; Rahmad Gurusinga; Diah Evawanna Anuhgera (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2021)
Menstruation is periodic and cyclical bleeding from the uterus accompanied by the release (desquamation) of the endometrium. Menstrual bleeding is the result of a complex interaction involving the hormonal system with the body's organs, namely the hypothalamus, pituitary, ovaries and uterus. Every woman experiences menstruation with a different cycle. The cause of irregular menstruation is from genetics and from a bad lifestyle. The purpose of this paper is to provide health education between brainstorming methods and simulation games to increase knowledge about menstruation. Participants in the Health education were 66 grade X students at SMA Negeri Beringin. In the implementation of activities using an instrument (questionnaire) to collect data. related to increasing knowledge about menstruation. The conclusion of this activity is that health education using simulation game and brain storming methods can increase adolescent knowledge about menstruation in class X students at SMA Negeri Beringin.